2012
DOI: 10.1530/ec-12-0033
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D and parathyroid hormone in relation to plasma B-type natriuretic peptide: the Hoorn Study

Abstract: ObjectiveA disturbed vitamin D–parathyroid hormone (PTH)–calcium axis may play a role in the pathogenesis of heart failure. Therefore, we investigated whether lower 25-hydroxyvitamin D (25(OH)D) and higher PTH are cross sectionally and after 8 years of follow-up associated with higher B-type natriuretic peptide (BNP) levels in older men and women.Design and methodsWe measured baseline 25(OH)D, PTH, and BNP in 502 subjects in 2000–2001 in the Hoorn Study, a population-based cohort. Follow-up BNP was available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Vitamin D status was assessed by measuring serum 25OHD concentrations with a competitive binding protein assay (DiasSorin) (25). Plasma B-type natriuretic peptide (BNP), a sensitive marker of ventricular dysfunction, was determined using an immunoradiometric assay (Shionoria, Osaka, Japan) (27). We measured LV mass as an estimate of myocardial structure using echocardiography (21).…”
Section: Additional Measurements At Baselinementioning
confidence: 99%
“…Vitamin D status was assessed by measuring serum 25OHD concentrations with a competitive binding protein assay (DiasSorin) (25). Plasma B-type natriuretic peptide (BNP), a sensitive marker of ventricular dysfunction, was determined using an immunoradiometric assay (Shionoria, Osaka, Japan) (27). We measured LV mass as an estimate of myocardial structure using echocardiography (21).…”
Section: Additional Measurements At Baselinementioning
confidence: 99%
“…16 Hypertension, prior CVD 15 and an estimate of kidney function-glomerular filtration rate-were calculated as previously described. 20 All participants, except those with previously diagnosed diabetes, underwent a standard 75 g oral glucose tolerance test to assess glucose status and were then classified into normal, impaired glucose metabolism or type 2 diabetes according to the 2006 World Health Organization criteria. 21 Participants filled out questionnaires to obtain information on medication use, smoking status, education level and physical activity.…”
Section: Additional Measurementsmentioning
confidence: 99%
“…Other prior studies generally have not found cross‐sectional associations of vitamin D with BNP or NT‐proBNP. In cross‐sectional analyses, 25(OH)D was not associated with BNP in the Hoorn study (older general population of white men and women), in a population of CHD patients, or in dialysis patients . In the Cardiovascular Health Study, 25(OH)D was inversely associated with NT‐proBNP in unadjusted analyses but not in analyses adjusted for demographic and CVD risk factors .…”
Section: Discussionmentioning
confidence: 91%
“…Whether low vitamin D levels are associated with subclinical myocardial damage and wall stress is not well established. Prior cross‐sectional studies have shown conflicting results . To our knowledge, however, there have been no prospective population‐based studies evaluating the association of low vitamin D with changes in levels of hs‐cTnT or NT‐proBNP.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation